Classifying Lalo languages: subgrouping, phonetic distance, and intelligibility - Yang, Cathryn (2024)
Lalo is a Central Ngwi (Loloish) language cluster spoken in western Yunnan, China by fewer than 300,000 speakers. Previously, most Lalo varieties were undocumented, and Lalo was thought to have only two dialects. This paper presents the first rigorous classification of Lalo languages, based on a dialectological study conducted in eighteen Lalo villages, which included the recording of 1,001-item vocabularies, comprehension tests, and sociolinguistic interviews. Synthesizing results from diachronic subgrouping, intelligibility, and phonetic distance measured by Levenshtein distance, this paper argues that the Lalo cluster actually comprises at least seven closely related languages. Phonetic distance correlates strongly with comprehension, and the NeighborNet network based on phonetic distance concurs with the diachronic subgrouping at shallow time depths, providing further validation of the dialectometric techniques. This paper suggests that such techniques are useful in the classification of lesser-known, endangered, indigenous languages, which often have an urgent need for language maintenance efforts.